2016
DOI: 10.1002/cphc.201501182
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Bonds in Low‐Molecular‐Weight Polyethylene Glycol

Abstract: We used static DFT calculations to analyze, in detail, the intramolecular hydrogen bonds formed in low-molecular-weight polyethylene glycol (PEG) with two to five repeat subunits. Both red-shifted O-H⋅⋅⋅O and blue-shifting C-H⋅⋅⋅O hydrogen bonds, which control the structural flexibility of PEG, were detected. To estimate the strength of these hydrogen bonds, the quantum theory of atoms in molecules was used. Car-Parrinello molecular dynamics simulations were used to mimic the structural rearrangements and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…More weak bonding broke as a higher temperature was introduced. From a previous study, it was found that there were two weak intramolecular interactions, that is, O‐H···O and C‐H···O hydrogen bonds, which manage the flexibility of PEG . Therefore, in general, a storage modulus decrease at a temperature below the melting point of a polymer‐based composite is due to the breakage of weak bonds in the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…More weak bonding broke as a higher temperature was introduced. From a previous study, it was found that there were two weak intramolecular interactions, that is, O‐H···O and C‐H···O hydrogen bonds, which manage the flexibility of PEG . Therefore, in general, a storage modulus decrease at a temperature below the melting point of a polymer‐based composite is due to the breakage of weak bonds in the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The observed downfield shifts of PEG in the PEG/LiClO 4 /D 2 O mixtures are because of the breaking of intermolecular and intramolecular ─HCH⋯OCH 2 hydrogen‐bonded structure, suggesting that the H‐bonded structure of PEG molecules are greatly perturbed when the temperature of the medium is increased. The conformational changes occurring in PEG are due to the reorganization of the strong O─H⋯O and weak C─H⋯O H‐bond, which is also in support of this statement . Increasing the temperature of the medium results in a breakage of these intermolecular and intramolecular hydrogen‐bonded networks and consequently increases the polymer interactions with the D 2 O molecules through the weak D 2 O⋯HCH─ and strong O─D⋯OCH 2 H‐bonding interactions …”
Section: Resultsmentioning
confidence: 55%
“…The conformational changes occurring in PEG are due to the reorganization of the strong O─H⋯O and weak C─H⋯O H‐bond, which is also in support of this statement . Increasing the temperature of the medium results in a breakage of these intermolecular and intramolecular hydrogen‐bonded networks and consequently increases the polymer interactions with the D 2 O molecules through the weak D 2 O⋯HCH─ and strong O─D⋯OCH 2 H‐bonding interactions …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations